Associations of dietary patterns with blood pressure and markers of subclinical arterial damage in adults with risk factors for CVD. Issue 18 (16th December 2021) - Tzelefa, Vicky; Tsirimiagkou, Christiana; Argyris, Antonios; Moschonis, George; Perogiannakis, George; Yannakoulia, Maria; Sfikakis, Petros; Protogerou, Athanase D; Karatzi, Kalliopi
Abstract: Objective: Unhealthy diet is a modifiable risk factor leading to subclinical arterial damage (SAD), high BP and CVD. It was aimed to investigate the possible associations of dietary patterns (DPs) with SAD in adults having multiple CVD risk factors. Design: Dietary intake was evaluated through two 24-h dietary recalls and principal component analysis was used to identify DPs. Oscillometry, applanation tonometry with pulse wave analysis and carotid ultrasound were used to assess peripheral and aortic BP, arterial stiffness and pressure wave reflections. Setting: Laiko University Hospital, Athens, Greece. Participants: A total of 470 individuals (53·1 ± 14·2 years) with CVD risk factors were enrolled. Results: A pattern characterised by increased consumption of whole-grain cereals, white meat and reduced consumption of sugar was positively associated with common carotid compliance ( β = 0·01, 95 % CI 0·00, 0·01), whereas a pattern high in refined cereals, red and processed meat was positively associated with brachial but not aortic systolic pressure ( β = 1·76, 95 % CI 0·11, 3·42) and mean arterial pressure (MAP) ( β = 1·18, 95 % CI 0·02, −2·38). Low consumption of low-fat dairy products, high consumption of full-fat cheese and butter was positively associated with MAP ( β = 0·97, 95 % CI 0·01, 1·95). Increased consumption of vegetables, fruits, fresh juices, fish and seafood was inversely associated with augmentation index (AIx) ( β = -1·01, 95 % CI -1·93, −0·09). Conclusion: Consumption of whole grains, white meat, fruits/vegetables, fish/seafood and avoidance of sugar was associated with improved SAD. Preference in refined grains, red/processed meat, high-fat cheese/butter and low intake of low-fat dairy products were associated with BP elevation. Future studies are needed to confirm the present findings.